Rewetting Drops Containing Surface Active Agents Improve the Clinical Performance of Silicone Hydrogel Contact Lenses - SUBBARAMAN, LAKSHMAN N.; BAYER, SIMONE; GEPR, STAATL; GLASIER, MARY-ANN; LORENTZ, HOLLY; SENCHYNA, MICHELLE; JONES, LYNDON (Optometry and vision science, 2006)
The purpose of this study was to investigate the impact of using a rewetting drop (RWD) containing surface active agents (OPTI-FREE RepleniSH; Alcon, Fort Worth, TX) on the clinical performance and protein deposition when using a continuous-wear (CW) silicone hydrogel (SH) contact lens. Subjects wore lotrafilcon A SH lenses on a 30-day CW basis for two consecutive 1-month periods while inserting either 0.9% unpreserved unit-dose saline (control) or multidose OPTI-FREE RepleniSH (test RWD). Subjective comfort and symptoms were assessed after 2 and 4 weeks with each product. After 1 month of wear with each product, lenses were collected and analyzed in the laboratory for total protein, total lysozyme, and percentage of denatured lysozyme. Symptoms of dryness and comfort varied across the day regardless of drop type (p < 0.001) with dryness being maximal on waking, least in the middle of the day, and increased towards the evening. The test RWD provided greater comfort on insertion (p = 0.02), better visual quality (p < 0.01), and less mucous discharge on waking (p = 0.02) than the control product. Lysozyme deposition was significantly reduced after the use of the test RWD as compared to saline (0.73 +/- 0.5 microg/lens vs. 1.14 +/- 0.7 microg/lens; p < 0.001) as was total protein deposition (1.17 +/- 0.7 microg/lens vs. 1.86 +/- 0.8 microg/lens; p < 0.001). Lysozyme denaturation was also reduced with the use of the test RWD compared with the control (76 +/- 10% vs. 85 +/- 7%; p < 0.01). The use of a RWD containing surface active agents provided greater subjective satisfaction, reduced lysozyme and total protein deposition, and reduced denatured lysozyme than a RWD containing saline alone.